THE IMPLEMENTATION OF EXCHANGE OF INFORMATION IN THE BANKING INDUSTRY - FIRLY ROSALINI; MARIA R.U.D. TAMBUNAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study aims to analyze the implementation of Automatic Exchange of Information by Financial Institution especially at PT Bank XYZ Indonesia, a subsidiary of bank that serves over 38 million customers covers 66 countries worldwide, in Europe, Asia, the Middle East, and North Africa, North and Latin America. This study uses a qualitative approach with data collection through library and field research conducted by interviews with related parties. The results of the study show that Bank XYZ as a Reporting Financial Institution is required to implement the provisions of international reporting standards, namely Common Reporting Standard (CRS), which is used to classify data in accordance with its reporting objectives. Some obstacles were found, namely the need for further guidance issued by the Directorate General of Taxes as a competent authority that regulates in more detail the instructions for filling in reports to be reported when reporting financial information data, and also the Directorate General of Taxes must anticipate the possibility related problems when reported by the reporting financial institution.